Next-generation firewall: implementando funcionalidades utilizando Snort e OpenAppID - XAVIER, José Deivison Vieira (2019)
Identify application traffic is one of the main features present in a Next-Generation Firewall. This work implements the identification of the traffic of applications cataloged using the tools open source Snort and OpenAppID, also uses the language "Lua" for the identification of applications not cataloged. Tests were performed to demonstrate the operation and limitations. The results showed that it is possible to identify applications using the aforementioned tools, with the possibility of including new applications.